Workshop-Based Learning Versus Project-Based Learning: Which One is the Best for the English Writing Ability - Mustain, Mustain (Penerbit STKIP PGRI Bangkalan, 2018)
This research focuses on the investigation between workshop-based learning versus project based learning: which one is the best for the English writing ability through true-experimental in the randomize-pretest-posttes control group design. The population of this study were 160 participants or students of the English Department in certain Bangkalan university and they were randomly 60 students selected to be a sample of this research through simple random sampling. The proses of sampling, in this case, the researcher is to ensure that each and every member of the population has an equal chance of being selected through lottere method. Then researcher randomized the sample each 30 students to assign the two groups, experimental group and control group.The instrument of this research were in the form of test. The subjective test were individually distributed to students where they wrote paragraph at least 150 words by the time allocation 90 minutes. The topic is indiviually choosen by the participants based on their own ideas. Since the Independent T-test was done to administrate in the data collection through SPSS 22 as data processing media in the level of significance of 5%. Based on the collected above, this research shown due to the t-value was higher than t-table (5.816 > 1.701); It meant that, the differences of the writing ability between the use of Workshop-Based Learning and Project-based learning were significant. It is concluded the students are taught by workshop-based learning have better writing ability than the students who taught by project-based learning. It meant that there is the effect of workshop-based learning on the students’ writing English ability in Bangkalan. With regard to the results of research, the researcher suggest that the research should be reconducted in the future studies by other researchers comprehensively in terms of sampling, treatment, time and others.